PHYTOREGULATORS AND GERMINATION OF SWEET PASSION FRUIT SEEDS UNDER LABORATORY CONDITIONS - ZUCARELI, C.; CASTRO, M.M.; OLIVEIRA, H.R.; BRANCALIÃO, S.R.; RODRIGUES, J.D.; ONO, E.O.; BOARO, C.S.F. (Scientia Agraria, 2003)
The experiment was carried out in Seed Analyze Laboratory of Department of Crop Science of São Paulo State University (UNESP) Botucatu, Brasil. The objective of the experiment was to study the influence of phytoregulators on the germination of Passiflora alata Curtis seeds. Completely randomized blocks, with four replications, 14 treatments of 50 seeds per plot was the experimental design used in the assay. The treatments was composed by applications of GA3, phenylmethil-tetrahydro-pyranil-aminopurine, and ethephon phytoregulators on dosages of 75 and 150 mg L-1 and in combinations of couples of thoses. In the treatments were used two controls, being one with seeds only soaked in distilled water and, the other seeds that did not receive any treatment. The evaluations of initial root emission, percentage of normal seedling, and percentage of hard seeds were avaluated by germination test under 25 °C temperature, during 35 days and after the seeds were remained more 35 days under 20-30 °C temperature. GA3, N-phenylmethyl-9- tetra-hydro-2H-2 pyranil 9H-6 aminopurine, and ethephon phytoregulators, on the 75 and 150 mg L-1 dosages did not favor the process of P.alata seed germinations.